MANAJEMEN PENERIMAAN RETRIBUSI PELAYANAN PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN JOMBANG - Anggraini, Aristyana Vira; Widiyarta, Agus (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Regional Original Revenue (PAD) played an important role in financing the region, so a good management system was needed to realize more optimal PAD revenue. Besides taxes, the PAD component with the largest revenue was the regional levy. However, Jombang Regency's regional levy receipts decreased from 2018 to 2022. Therefore, good revenue management was needed in the scope of levy, namely market service levy. The purpose of this study was to describe the management of market service levy receipts carried out by the government to increase revenue. This research method was descriptive with a qualitative approach. The focus of this research was the basic principles of regional revenue management by Mahmudi (2020), including (1) expanding the revenue base, (2) controlling revenue, (3) improving the efficiency of revenue administration, and (4) transparency and accountability. The results of this study showed that the management of market service levy receipts had been well managed.